Electrophysiological Correlates of the Effect of Task Difficulty on Inhibition of Return - Li, Ai-Su; Miao, Cheng-Guo; Han, Yu; He, Xun; Zhang, Yang (Frontiers in Psychology, 2018)
Inhibition of return (IOR) refers to slower responses to targets that occur at a previously attended location than to those at control locations. Previous studies on the impact of task difficulty on IOR have shown conflicting results. However, these studies failed to match low-level characteristics of stimuli (e.g., size, color, and luminance) across difficulty levels, and so might have confounded the effect of task difficulty with that of stimulus characteristics. Hence, whether and how task difficulty modulates IOR remain largely unknown. This study utilized the event-related potentials (ERPs) technique in combination with a cue-target paradigm to tackle this question. Task difficulty was manipulated by changing the position of a gap in a rectangle stimulus, while stimulus size, color, and luminance were precisely matched. IOR was observed in reaction times across all difficulty levels but was found in accuracy at the medium level only. The modulation effect of task difficulty on IOR was also evident in the N1 and P2 ERP components, which showed significantly weaker IOR effects at the medium difficulty level than at the easy and hard levels. It is suggested that the modulation of IOR by task difficulty involves both perceptual and post-perceptual processes.